Implementasi Merdeka Belajar Kampus Merdeka - Zico Fakhrur Rozi; Rambat Nur Sasongko (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the Implementation of Free Campus Independent Learning (MBKM) in the Mathematics and Natural Sciences Department of PGRI Silampari University. The method used is a survey by distributing questionnaires. Respondents in this study were 173 students of the Mathematics and Natural Sciences Department at PGRI Silampari University, which consisted of the Study Programs for Mathematics Education, Physics Education and Biology Education. The results showed that as many as 68.2% of students strongly agreed that the Mathematics and Natural Sciences Department had MBKM activities; 98.8% are interested in participating in MBKM activities; and apprenticeship/practice activities are activities that students are most interested in (29.5%); and 100% of MIPA Department students think that the MBKM program provides additional competencies for students according to future needs and can improve student soft-skills. In conclusion, the Mathematics and Natural Sciences Department of PGRI Silampari University has carried out MBKM activities that can provide additional competencies for students. Keywords: Implementation, Independent Campus, Free Learning, PGRI Silampari University